Edukasi Pemanfaatan Keuangan Digital Dikalangan Remaja SMK Techno Media - Karlina, Lilis; Nursita, Meta; Astuti, Reni (Jurnal Abdi Citra, 2024)
Digitalization brings new business models and players, and changes consumer behavior and the economic-financial landscape. New business models that prioritize convenience are quickly accepted by society. Digitalization also gives rise to a new paradigm regarding data which is not only seen as contributing to the creation of innovation and increased efficiency. These fundamental changes provide a policy challenge, namely to find a balance point between efforts to optimize digital innovation opportunities and mitigate emerging risks. Techno Media Vocational School is a broadcasting vocational school which carries out its activities under the auspices of the Ministry of Education and Culture. Techno Media Vocational School in the implementation of its education has utilized several electronic media in it and digitalization for the world of education is very useful for preparing a generation that is competitive in the 4.0 era. The community service team's activities are carried out in a measurable manner with the output target being that Techno Media Vocational School students expand their knowledge and digitalization processes which are increasingly developing rapidly in the 4.0 era and provide the best solutions in choosing the use of digitalization in the 4.0 era. The results of activities in the context of community service will be published in a community service journal. Digitalisasi menghadirkan model bisnis dan pemain baru, serta mengubah perilaku konsumen dan lanskap ekonomi-keuangan. Model bisnis baru yang mengedepankan kemudahan, secara cepat diterima oleh masyarakat, Digitalisasi juga memunculkan paradigma baru tentang data yang bukan saja dipandang berkontribusi pada terciptanya inovasi dan peningkatan efisiensi, Perubahan mendasar tersebut memberikan tantangan kebijakan yaitu untuk mencari titik keseimbangan antara upaya mengoptimalkan peluang inovasi digital dengan memitigasi risiko-risiko yang muncul. SMK Techno Media merupakan sekolah kejuruan ilmu broadcasting yang dalam pelaksanaan kegiatannya dibawah naungan kementrian Pendidikan dan kebudayaan. SMK Techno Media dalam pelaksanaan pendidikannya telah memanfaatkan beberapa media elektronik didalamnya dan digitalisasi bagi dunia pendidikan sangat bermanfaat untuk menyiapkan generasi yang berdaya saing di era 4.0. Kegiatan tim pengabdian masyarakat dilakukan secara terukur dengan target luaran menjadikan para siswa-siswi SMK Techno Media Memperluas pengetahuan dan proses digitalisasi yang semakin berkembang cepat di era 4.0 dan memberikan solusi terbaik dalam memilih penggunaan digitalisasi di era 4.0. Hasil dari kegiatan dalam rangka pengabdian kepada masyarakat ini akan dipublikaskan dalam sebuah jurnal pengabdian masyarakat.